DEVELOPING CLASSDOJO AS E-LEARNING MEDIA OF WRITING DESCRIPTIVE TEXT FOR GRADE TENTH STUDENTS AT MAN 2 DELI SERDANG - Dwita Widya Sari; Rahmad Husein (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
The objective of this study was to develop e-learning media by using ClassDojo forgrade tenth at MAN 2 Deli Serdang. This study was conducted by using Research andDevelopment design through six stages; gathering data and information, needanalysis, designing materials and media, validating, revising (final product). Thesubject of the study was grade tenth of MAN 2 Deli Serdang. The data were gatheredby reviewing documents, conducting interview to English teacher and distributtingquestionnaire to X MIA 3 consists of 31 students to get the students’ need. Theinterview and questionnaire result prove that the students need more interesting andup to date media to learn writing descriptive text. The developed writing media werevalidated by two experts which are the average scores (4.55 and 4.05) show that themedia are valid and suitable to use for grade tenth students of MAN 2 Deli Serdang.The result of product distributed to the students through ClassDojo.